Analisis tipe kepemimpinan profetik Kepala Perpustakaan Universitas Muhammadiyah Yogyakarta - Ifonilla Yenianti (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
Head of the Library of Muhammadiyah University (UMY), as well as the author of books about library management, namely Lasa H.S. is a teacher, father, and role model for future librarians. His peak career as the main librarian became his extraordinary dedication at the Library of Gadjah Mada University (UGM) Yogyakarta. Lasa H.S.'s motivational quotes namely